Politics and history of violence and crime in Central America - Huhn, Sebastian (Palgrave Macmillan, 2020)
Contents: 1. The enigma of violent realities in Central America : towards a historical perspective Sebastian Huhn and Hannes Warnecke-Berger -- 2. How to explain and how not to explain contemporary criminal violence in Central America Heidrun Zinecker -- 3. Of Pandillas, Pirucas, and Pablo Escobar in the Barrio Dennis Rodgers -- 4. Memories of violence in the Salvadoran Civil War Erik Ching -- 5. Questioning the crime wave Sebastian Huhn -- 6. The Salvadoran armed left and revolutionary violence (1970-1980) Alberto Martín Álvarez and Eudald Cortina Orero -- 7. On collective violence in nineteenth-century Guatemala Michael Riekenberg -- 9. Borderlands and public violence in a shadow polity Robert H. Holden -- 9. Forms of violence in past and present : El Salvador and Belize in comparative perspective Hannes Warnecke-Berger -- 10. The violence of dispossession : Guatemala in the nineteenth and twentieth centuries Jim Handy.